Digital literacy, attitudes toward e-learning, and task value roles in college students’ distance learning self-regulation - Muasyaroh, Husnul; Royanto, Lucia R.M. (Psychological Research on Urban Society, 2024)
The increased adoption of distance learning in higher education, which was especially evident in urban areas during the COVID-19 pandemic, underscores the crucial role of self-regulated learning (SRL) skills. Although previous research demonstrated positive correlations between learner factors and SRL in distance education, a research gap exists in understanding the mediating and moderating roles of specific factors. This study addresses this concern by examining the relationship between digital literacy and SRL as mediated by attitude toward e-learning with task value as a moderator. The study recruited 538 college students (aged 17–25 years) from 10 public universities. Digital literacy was measured using the Self-perceived Evaluations of Digital Literacy Competencies. We measured attitudes toward e-learning using the E-Learning Attitudes Questionnaire. This study also used the Subjective Task Value instrument to measure task value and the Self-Regulated Online Learning Scale to measure SRL. The results indicate that task value significantly strengthened the relationship between digital literacy and SRL through the mediating role of attitudes toward e-learning. Hence, digital literacy can support SRL through the mediation of attitudes toward e-learning and is strengthened by the task values of college students in distance learning.